HepGentox: a novel promising HepG2 reportergene-assay for the detection of genotoxic substances in complex mixtures - Elisabeth Pinter; Christina Friedl; Alexandra Irnesberger; Thomas Czerny; Tina Piwonka; Alfonso Peñarroya; Manfred Tacker; Elisabeth Riegel (PeerJ, 2021)
Background In risk assessment, genotoxicity is a key factor to determine the safety for the consumer. Most in vitro genotoxicity assays were developed for the assessment of pure substances. However, in recent years more attention has been given to complex mixtures, where usually low amounts of a substance are present. For high-throughput screening, a toxicologically sensitive assay should be used, covering a broad range of genotoxic substances and detecting them at low concentrations. HepG2 cells have been recommended as one of the prime candidates for genotoxicity testing, as they are p53 competent, less prone towards cytotoxic effects and tend to have some metabolic activity. Methods A HepG2 liver cell line was characterized for its suitability for genotoxicity assessment. For this, a luciferase based reporter gene assay revolving around the p53 pathway was validated for the analysis of pure substances and of complex mixtures. Further, the cell’s capability to detect genotoxins correctly with and without an exogenous metabolizing system, namely rat liver S9, was assessed. Results The assay proved to have a high toxicological sensitivity (87.5%) and specificity (94%). Further, the endogenous metabolizing system of the HepG2 cells was able to detect some genotoxins, which are known to depend on an enzymatic system. When complex mixtures were added this did not lead to any adverse effects concerning the assays performance and cytotoxicity was not an issue. Discussion The HepGentox proved to have a high toxicological sensitivity and specificity for the tested substances, with similar or even lower lowest effective concentration (LEC) values, compared to other regulatory mammalian assays. This combines some important aspects in one test system, while also being less time and material consuming and covering several genotoxicity endpoints. As the assay performs well with and without an exogenous metabolizing system, no animal liver fractions have to be used, which application is discussed controversially and is considered to be expensive and laborious in sample testing. Because of this, the HepGentox is suitable for a cost-efficient first screening approach to obtain important information with human cells for further approaches, with a relatively fast and easy method. Therefore, the HepGentox is a promising assay to detect genotoxic substances correctly in complex mixtures even at low concentrations, with the potential for a high throughput application. In a nutshell, as part of an in vitro bioassay test battery, this assay could provide valuable information for complex mixtures.